2012
DOI: 10.1080/09712119.2011.633880
|View full text |Cite
|
Sign up to set email alerts
|

Sensory analysis of full-, reduced- and low-fat cheese elaborated with raw goat milk

Abstract: 2012) Sensory analysis of full-, reduced-and low-fat cheese elaborated with raw goat milkThe market for goat milk cheese has grown due to the new tendencies to consume innovative products, and the fact that it has provided a profitable alternative to cow milk cheese due to its inherent health-promoting attributes. The trends toward healthier eating have increased the interest in low-fat cheese (LFC). The objective of this study is to enable an understanding and provides a baseline of the effect of fat reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The protein content of the Queso Costeño samples varied significantly (p < 0.05), decreasing from 24.96% to 20.36% according to the increase in fat percentage in milk. This behaviour is due to the fact that milk fat and moisture act as fillers in the casein matrix of Queso Costeño.This behavior was similar to the research reported by Sánchez-Macías et al, [36]. Van Hekken et al [37] found the same behavior in their study on the reduction of fat content in proteolysis and rheological properties of Cheddar cheese made from goat milk, in which they stated that moisture and protein content increase when the fat percentage is low.…”
Section: Physicochemical Propertiessupporting
confidence: 87%
“…The protein content of the Queso Costeño samples varied significantly (p < 0.05), decreasing from 24.96% to 20.36% according to the increase in fat percentage in milk. This behaviour is due to the fact that milk fat and moisture act as fillers in the casein matrix of Queso Costeño.This behavior was similar to the research reported by Sánchez-Macías et al, [36]. Van Hekken et al [37] found the same behavior in their study on the reduction of fat content in proteolysis and rheological properties of Cheddar cheese made from goat milk, in which they stated that moisture and protein content increase when the fat percentage is low.…”
Section: Physicochemical Propertiessupporting
confidence: 87%
“…Murciano‐Granadina cheeses had a larger fat content and a lower pH than the Malagueña ones (De la Haba Ruiz et al ., ), the latter constituent of the milk being the one most influencing the development of the characteristic flavour of the cheeses (Mcsweeney & Sousa, ). Thus, the cheeses with a higher fat content had greater odour/aroma intensity (Pizzillo et al ., ; Morand‐Fehr et al ., ; Sanchez‐Macias et al ., ).…”
Section: Resultsmentioning
confidence: 98%
“…Murciano-Granadina cheeses had a larger fat content and a lower pH than the Malagueña ones (De la Haba Ruiz et al, 2016), the latter constituent of the milk being the one most influencing the development of the characteristic flavour of the cheeses (Mcsweeney & Sousa, 2000). Thus, the cheeses with a higher fat content had greater odour/aroma intensity (Pizzillo et al, 2005;Morand-Fehr et al, 2007;Sanchez-Macias et al, 2012). The type of coagulant had an independent effect on the overall aroma intensity, the salty taste, the sensation of piquancy and on all the texture attributes except friability (Tables 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…The sensory analyses were performed in a special room following the instructions given by the norm ISO 8589 (2007), according to the guidelines followed by Sa´nchez-Macias et al (2012). The first test was a descriptive analysis (ISO 4121, 2003) in which a trained 12-member tasting panel was used.…”
Section: Sensory Analysismentioning
confidence: 99%